2016
DOI: 10.1002/nbm.3499
|View full text |Cite
|
Sign up to set email alerts
|

Overhauser‐enhanced magnetic resonance elastography

Abstract: Magnetic resonance elastography (MRE) is a powerful technique to assess the mechanical properties of living tissue. However, it suffers from reduced sensitivity in regions with short T2 and T2 * such as in tissue with high concentrations of paramagnetic iron, or in regions surrounding implanted devices. In this work, we exploit the longer T2 * attainable at ultra-low magnetic fields in combination with Overhauser dynamic nuclear polarization (DNP) to enable rapid MRE at 0.0065 T. A 3D balanced steady-state fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…MRE is a highly accurate technique for the staging of liver fibrosis, but it is affected by a technical failure rate of 5.6%, especially in patients with iron deposition . Investigational sequences may improve coverage, robustness to iron deposition, and technical success …”
Section: Future Directionsmentioning
confidence: 99%
“…MRE is a highly accurate technique for the staging of liver fibrosis, but it is affected by a technical failure rate of 5.6%, especially in patients with iron deposition . Investigational sequences may improve coverage, robustness to iron deposition, and technical success …”
Section: Future Directionsmentioning
confidence: 99%
“…This other report also studied the differences in failure rates between the two field strengths, and indicated that the higher field strength was associated with significantly more technical failures (15% at 3.0 T versus 3.5% at 1.5 T). Overhauser‐enhanced MRE, by virtue of its operation at low magnetic field strength and theoretically benefiting from longer T 2 * in patients with iron overload, could prove beneficial …”
Section: Validation Studiesmentioning
confidence: 99%
“…Most current volumetric MRE acquisitions are performed using sequential or interleaved stacked 2D scans. Multislab acquisition was recently developed and applied in conjunction with spiral MRE readout, whereas full 3D acquisition was also recently performed together with compressed sensing and dynamic nuclear polarization MRE …”
Section: Advanced Readout and Sub‐nyquist Techniquesmentioning
confidence: 99%
“…The randomness of the sampling pattern leads to noise‐like interference, which can be filtered in the sparse domain of the MRI images by non‐linear thresholding . CS has recently been used in ultra‐low field MRE in conjunction with dynamic nuclear polarization (DNP) . Here, Cartesian 3D acquisition with phase encoding in both phase and slice encoding directions was paired with variable density Gaussian undersampling patterns .…”
Section: Advanced Readout and Sub‐nyquist Techniquesmentioning
confidence: 99%